Machine Translation Literacy as a Social Responsibility - Bowker, Lynne (Université d'Ottawa | University of Ottawa, 2019)
Machine translation is easily accessible and easy to use, but this doesn’t mean that everyone uses it in an informed way. We suggest that translators have a social responsibility for helping people outside the language professions to become informed users of machine translation, and that partnering with libraries could provide a means of reaching and educating a broad cross-section of citizens. We briefly summarize key elements of a machine translation literacy workshop that we piloted with two academic libraries, and we outline our plans for the next phase of the project with a public library.
Keywords: Machine translation; Machine translation literacy; Social responsibility; Ethic of care; Libraries